Analyzing workplace deviance in modern organizations - Sharma, Naman, 1986- (Advances in human resources management and organizational development (AHRMOD) book series., 2020)
"This book addresses issues related to employee deviance within and outside the organizations. It explores organizational behavior issues, challenges, and solutions. It also examines best employee engagement practices"--